Limiting Trigo...

Calculus Level 4

Evaluate the following expression :

l i m x 0 ( ( 1 c o s x ) + ( 1 c o s x ) + ( 1 c o s x ) + . . . . . . . . . ) 1 x 2 \underset { x\rightarrow 0 }{ lim } \frac { \left( \sqrt { \left( 1-cos\quad x \right) +\sqrt { \left( 1-cos\quad x \right) +\sqrt { \left( 1-cos\quad x \right) +.........\infty } } } \right) -1 }{ { x }^{ 2 } }

To try more such problems click here .

None of the above. 2 1 Imaginary Solution. 1 2 \frac{1}{2} 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let y = α + α + α + . . . . . . y\quad =\quad \sqrt { \alpha +\sqrt { \alpha +\sqrt { \alpha +......\infty } } }

where α = 1 c o s x \alpha = 1 - cos \quad x ; a s x 0 , a 0 as \quad x\rightarrow 0, a \rightarrow 0

y = α + y ; y 2 = α + y y 2 y α = 0 y=\sqrt{\alpha +y}; y^{2}=\alpha +y \Rightarrow y^{2}-y-\alpha=0 y = 1 ± 4 + α 2 ( N e g l e c t i n g v e s i g n , a s y c a n t b e v e ) y\quad =\quad \frac { 1\pm \sqrt { 4+\alpha } }{ 2 } \quad \quad (Neglecting\quad -ve\quad sign,\quad as\quad y\quad can't\quad be\quad -ve) y = 1 + 4 + α 2 y\quad =\quad \frac { 1 + \sqrt { 4+\alpha } }{ 2 } \quad N o w , Now, y = l i m x 0 α 0 [ 1 + 1 + 4 α 2 1 ] x 2 1 c o s x ( 1 c o s x ) = l i m α 0 1 + 4 α 1 2.2. α ( A s l i m x 0 x 2 1 c o s x = 2 ) \quad \quad y\quad =\underset { \begin{matrix} x\rightarrow 0 \\ \alpha \rightarrow 0 \end{matrix} }{ lim } \frac { \left[ \frac { 1+\sqrt { 1+4\alpha } }{ 2 } \quad -1 \right] }{ \frac { { x }^{ 2 } }{ 1-cos\quad x } (1-cos\quad x) } =\underset { \alpha \rightarrow 0 }{ lim } \frac { \sqrt { 1+4\alpha } \quad -1 }{ 2.2.\alpha } \quad \quad \left( As\quad \underset { x\rightarrow 0 }{ lim } \frac { { x }^{ 2 } }{ 1-cos\quad x } =2 \right)

= l i m α 0 ( 1 + 4 α ) 1 4 α ( 1 + 4 α + 1 ) \quad =\quad \underset { \alpha \rightarrow 0 }{ lim } \frac { (1+4\alpha )\quad -1 }{ 4\alpha \left( \sqrt { 1+4\alpha } +1 \right) }

= l i m α 0 1 1 + 4 α + 1 = 1 2 \quad =\quad \underset { \alpha \rightarrow 0 }{ lim } \frac { 1 }{ \sqrt { 1+4\alpha } +1 } \quad =\quad \boxed{\frac { 1 }{ 2 }}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...